Genetic diversity of provitamin-A cassava (Manihot esculenta Crantz) in Sierra Leone - Kamanda, I.; Blay, E.T.; Asante, I.K.; Danquah, A.; Ifie, B.E.; Parkes, Elizabeth Y.; Kulakow, Peter A.; Rabbi, Ismail Y.; Conteh, A.; Kamara, J.S.; Mensah, H.K.; Whyte, J.B.A.; et al. (Springer, 2020)
Understanding the genetic diversity among accessions and germplasm is an important requirement for crop development as it allows for the selection of diverse parental combinations for enhancing genetic gain in varietal selection, advancement and release. The study aimed to characterize 183 provitamin A cassava (Manihot esculenta Crantz) accessions and five Sierra Leonean varieties using morphological traits, total carotenoid content and SNP markers to develop a collection for conservation and further use in the cassava breeding program. Both morphological parameters and 5634 SNP markers were used to assess the diversity among the provitamin-A cassava accessions and varieties. Significant differences were observed among the accessions for most of the traits measured. The first five PCs together accounted for 70.44% of the total phenotypic variation based on yield and yield components among the 183 provitamin-A cassava accessions and five Sierra Leonean varieties. The present study showed that provitamin-A cassava accessions in Sierra Leone have moderate to high diversity based on morphological and molecular assessment studies. The similarity index among the 187 and 185 cassava accessions grouped them into 6 and 9 distinct clusters based on morphological and molecular analyses, respectively. A significant positive, but low correlation (r = 0.104; p\0.034), was observed between the two dendrograms. The results obtained will serve as a guide and basis of germplasm management and improvement for total carotenoid content, yield and African cassava mosaic disease resistance in Sierra Leone.